Effects of increased feed intake or additional corn from day 30 to 50 of gestation on performance of sows and growth performance and carcass characteristics of offspring - R E Musser; J S Bauman; M Heintz; Robert D Goodband; Duane L Davis; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1997)
A total of 321 PIC sows was used to determine the effects of either increased feed (8 Ib/d of complete feed) or added corn (4 Ib/d of complete feed plus 4 Ib/d of ground corn) from d 30 to 50 of gestation on sow and offspring performance. Sows fed increased feed intake from d 30 to 50 of gestation had fewer pigs born live than control sows; however this decrease was not observed for sows fed ground corn. Increased complete diet feed intake from d 30 to 50 of gestation resulted in heavier offspring at slaughter, with offspring from sows fed additional corn being intermediate. Gilts from sows that were fed extra feed or corn had decreased 10th rib fat depth at market. Increased feed or addition of ground corn resulted in increased percentage lean and fat-free lean index for the sows' offspring. Although further research is needed to verify our results, they indicate that increased nutrient intake during critical periods in gestation can influence growth and carcass composition of the offspring.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Gestation; Offspring; Improved lean